2021
DOI: 10.31026/j.eng.2021.09.04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drinking Water Quality in Al Wahda Treatment Plant in Baghdad City- Iraq

Abstract: This study aims to evaluate drinking water quality at the Al Wahda plant (WTP) in Baghdad city. A conventional water treatment plant with an average flow rate of 72.82 MLD. Water samples were taken from the influent and effluent of the treatment plant and analyzed for some physicochemical and biological parameters during the period from June to November 2020. The results of the evaluation indicate that treated water has almost the same characteristics as raw water; in other terms, the plant units do not remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…1: C). These results agrees with those published by Darwesh (2014) and Danial et al (2014) when they found that BA was better than kinetin for fig trees multiplication stage.The reasons behind the positive role of cytokinins on the multiplication stage might be due to their profound role in releasing lateral buds from the dominance of terminal buds without the need to remove the apical bud by promoting formation of xylem tissues of buds which facilitate the transformation of water and nutrient leading to lateral bud growth (Mohammed & Al-Younis, 1991) On the other hand, Table (3) shows that the addition of 1.5 mg.l -1 BA to MS medium was significantly the best among the rest of the treatments except 3.5 mg.l -1 Kinetin in regard of number of shoots per explant. Since, 1.5 mg.l -1 BA recorded the highest values including 5.10 shoots/ explant, 12.00 leaves/ explant and the longest shoots (5.00 cm) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1: C). These results agrees with those published by Darwesh (2014) and Danial et al (2014) when they found that BA was better than kinetin for fig trees multiplication stage.The reasons behind the positive role of cytokinins on the multiplication stage might be due to their profound role in releasing lateral buds from the dominance of terminal buds without the need to remove the apical bud by promoting formation of xylem tissues of buds which facilitate the transformation of water and nutrient leading to lateral bud growth (Mohammed & Al-Younis, 1991) On the other hand, Table (3) shows that the addition of 1.5 mg.l -1 BA to MS medium was significantly the best among the rest of the treatments except 3.5 mg.l -1 Kinetin in regard of number of shoots per explant. Since, 1.5 mg.l -1 BA recorded the highest values including 5.10 shoots/ explant, 12.00 leaves/ explant and the longest shoots (5.00 cm) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings have been submitted regarding the beneficial effect of cytokinin (BAP) for pomegranate shoot proliferation using an MS medium (Patil et al, 2011;Mulaei et al, 2020 andChoudhary et al, 2022). The data obtained in apical dominance as a result of the precence of cytokinins in removing the apical dominance in the buds (Mohammed & Al-Younis, 1991;Al-Rifae'e & Al-Shobaki, 2002;Danial et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Auxins are the most suitable PGRs mainly used for adventitious root formation and inducing cell division through tissue culture technique. In nature, the hormones of this group are involved with stem and internodes elongation, apical dominance, leaf abscission, root induction, and tropism, (Mohammed & Al-Younis, 1991;Al-Rifae'e &Al-Shobaki 2002 andKumar et al, 2017). Thus, IBA auxin is considered the most important and the most effective of all auxin types, followed by NAA, that commonly used for in vitro root induction.…”
Section: Discussionmentioning
confidence: 99%
“…After taking in the data, the ANNs train themselves for the recognition of data patterns and providing outputs. The model consists of grouped artificial neurons representing the core units of the modelling process [12]. The model represents an alternative method to conventional water quality models through the provision of advanced predictions and forecasts [13,22].…”
Section: Introductionmentioning
confidence: 99%